Re-contextualising TPACK: exploring teachers' (non-)use of digital technologies. Issue 5 (19th October 2016) - Phillips, Michael
Abstract : Technological, pedagogical and content knowledge (TPACK) has been used by hundreds of studies as a theoretical framework to explore teachers' technology use in classroom settings. While these studies have contributed to understandings of the interplay between these different knowledge domains and the differences between pre- and in-service teachers' knowledge, little work has been done to examine the influence of teachers' socially mediated workplace settings on TPACK enactment. This article begins to address this issue reporting findings from an eight-month case study involving 10 teachers in an Australian secondary school. Results reported in this article indicate that TPACK enactment is influenced by processes of identity development and practice. These findings challenge the established position of knowledge as an epistemological possession inherent in the TPACK framework rather than also considering knowing as an epistemology of practice. Implications for in-service teachers and school authorities are discussed and suggestions for future research considered.